Effect of carbohydrate ingestion on glucose kinetics during exercise in the heat - Angus, Damien J; Febbraio, Mark A; Lasini, David; Hargreaves, Mark (Journal of applied physiology (1985), 2001)
1  Exercise Physiology and Metabolism Laboratory, Department of Physiology, The University of Melbourne, Parkville, Victoria 3052; and 2  School of Health Sciences, Deakin University, Burwood, Victoria 3125, Australia Six endurance-trained men [peak oxygen uptake ( O 2 ) = 4.58 ± 0.50 (SE) l/min] completed 60 min of exercise at a workload requiring 68 ± 2% peak O 2 in an environmental chamber maintained at 35°C (<50% relative humidity) on two occasions, separated by at least 1 wk. Subjects ingested either a 6% glucose solution containing 1 µCi [3- 3 H]glucose/g glucose (CHO trial) or a sweet placebo (Con trial) during the trials. Rates of hepatic glucose production [HGP =   glucose rate of appearance (R a ) in Con trial] and glucose disappearance (R d ), were measured using a primed, continuous infusion of [6,6- 2 H]glucose, corrected for gut-derived glucose (gut R a ) in the CHO trial. No differences in heart rate, O 2 , respiratory exchange ratio, or rectal temperature were observed between trials. Plasma glucose concentrations were similar at rest but increased ( P <   0.05) to a greater extent in the CHO trial compared with the Con trial. This was due to the absorption of ingested glucose in the CHO trial, because gut R a after 30 and 50 min (16 ± 5 µmol · kg 1 · min 1 ) was higher ( P < 0.05) compared with rest, whereas HGP during exercise was not different between trials. Glucose R d was higher ( P < 0.05) in the CHO trial after 30 and 50 min (48.0 ± 6.3 vs 34.6 ± 3.8 µmol · kg 1 · min 1 , CHO vs. Con, respectively). These results indicate that ingestion of carbohydrate, at a rate of ~1.0 g/min, increases glucose R d but does not blunt the rise in HGP during exercise in the heat. heat stress; liver glucose output; muscle glucose uptake